2000
DOI: 10.1042/cs0990421
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Japanese herbal medicine ‘Inchinko-to’ (TJ-135) on concanavalin A-induced hepatitis in mice

Abstract: Inchinko-to (TJ-135) is a herbal medicine consisting of three kinds of crude drugs, and in Japan it is administered mainly to patients with cholestasis. The present study evaluated the effects of TJ-135 on concanavalin A (con A)-induced hepatitis in mice in vivo and con A-induced cytokine production in vitro. When mice were pretreated with oral TJ-135 for 1 week before intravenous con A injection, the activities of serum aspartate aminotransferase (AST), alanine aminotransferase (ALT) and lactate dehydrogenase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…We decided the applied dose of ICKT referring from Yamashiki et al and Imanishi et al [5,12] reports. We prescribed pure extract ICKT (TJ-135).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We decided the applied dose of ICKT referring from Yamashiki et al and Imanishi et al [5,12] reports. We prescribed pure extract ICKT (TJ-135).…”
Section: Methodsmentioning
confidence: 99%
“…The daily amount of ICKT is 7.5 g/day in adults. Seven and one-half grams of this product contain 1.5 g of dried extract obtained from mixed raw herbs in the following ratio: 4.0 g of Inchinko (Artemisia Capillaries Spike), 3.0 g of San-shishi (JP Gardenia Fruit), and 1.0 g of Daio (JP Rhubarb Rhizome) [5][6][7][8].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Iinuma, et al reported that Inchinkoto might have a protective and antifibrotic effect for the liver of children with biliary atresia [6] [7]. Though the precise mechanisms of its action on the liver diseases remain unknown, it can be speculated as following: 1) inhibition of hepatocyte apoptosis induced by transforming growth factor-β1 [10]; 2) inhibition of the production of inflammatory cytokines and inducible nitric oxide synthase [11] [12]; and 3) direct suppression of liver fibrosis [13]. Despite the promising effects on diverse liver diseases without serious adverse effects, to the best of our knowledge, Inchinkoto has not previously been given to patients with LC characterized by diffuse nodular regeneration surrounded by fibrous bands [14].…”
Section: Discussionmentioning
confidence: 99%